MANAGEMENT OF EXCELLENCE IN A COOPERATIVE OF URBAN TRANSPORT OPERATORS - Carlos Moura da Cunha, Ivan (Journal of Interdisciplinary Debates, 2024)
The urban mobility systems of municipalities are made up of various transport, passenger and freight services and subsystems. The mode of public passenger transport, the main one, in many cases, is operated by buses belonging to urban transport companies, and by the complementary service, operated by small vehicles. The great challenge of this format is to establish the corporate culture in the associations of operators of small vehicles, accustomed to an almost artisanal model, practically an extension of the informal or clandestine operation previously carried out. This challenge can be overcome through the actions of the Government, encouraging the formation of cooperatives, formed by these permittees. It must be considered that a cooperative has different specificities from a capital company. The management bodies of transport systems should encourage the assimilation of the management culture, more precisely the Management ® Excellence Model, which is desirable for cooperatives to have the necessary conditions to operate properly in transport systems. Hence, the general objective of this work is to provide the technical, economic, financial and structural conditions for cooperatives to have sustainability as an economic activity. The methodology used was based on an empirical, inductive and exploratory study, with the presentation of a strategic business management model. With this, it is intended to establish a management model to be followed by any entity that has delegation of operation by the Government, which, without a doubt, will constitute a great innovation in the institutional relationship with these individual operators